Bianchi Type-VI0 Inflationary Model in Lyra Geometry (Journal of Scientific Research, 2022)
In this paper, we have studied Bianchi type metric in Lyra's geometry with scalar field and flat potential. The Einstein's field equations have been solved by taking the shear scalar in the model proportional to the expansion scalar, which leads to A = Bn, where A and B are metric functions and n is a positive constant. Also, we discuss some physical and geometrical features of the obtaining model.